Gasket and electrochemical device

The use of PTFE-based gaskets with specific properties addresses the challenge of achieving low water vapor permeability and chemical/heat resistance in electrochemical devices, enhancing their performance and reliability.

JP2025060572AActive Publication Date: 2025-04-10DAIKIN INDUSTRIES LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024170720
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-29
Filing Date
2024-09-30
Publication Date
2025-04-10
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing gaskets for electrochemical devices, such as lithium-ion batteries, face challenges in achieving excellent low water vapor permeability while maintaining chemical and heat resistance.

Method used

The development of gaskets using polytetrafluoroethylene (PTFE) with non-melting moldability and specific properties, including a water vapor permeability coefficient of 0.020g/1000hr or less, a specific gravity of 2.130 or more and 2.180 or less, and a crystallinity of 35-60%, to enhance low water vapor permeability and chemical/heat resistance.

Benefits of technology

The PTFE-based gaskets exhibit superior low water vapor permeability, maintaining high chemical and heat resistance, making them suitable for use in electrochemical devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060572000008
    Figure 2025060572000008
  • Figure 2025060572000009
    Figure 2025060572000009
  • Figure 2025060572000001
    Figure 2025060572000001
Patent Text Reader

Abstract

To provide a gasket having low water vapor permeability, and an electrochemical device using the same.SOLUTION: A gasket includes polytetrafluoroethylene that exhibits non-melt formability, and has a water vapor permeability coefficient of 0.020 g / 1000 hr or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a gasket and an electrochemical device. [Background technology]

[0002] 2. Description of the Related Art It is known to use resins such as perfluoroalkoxyalkane (PFA) as sealing members (gaskets) for electrochemical devices such as lithium ion secondary batteries (see, for example, Patent Documents 1 to 4). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-174732 A [Patent Document 2] International Publication No. 2020 / 066050 [Patent Document 3] International Publication No. 2014 / 049645 [Patent Document 4] Patent Publication No. 2021-141045 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present disclosure is to provide a gasket having excellent low water vapor permeability, and an electrochemical device using the same. [Means for solving the problem]

[0005] The present disclosure (1) is a gasket that contains polytetrafluoroethylene exhibiting non-melt moldability and has a water vapor permeability coefficient of 0.020 g / 1000 hr or less.

[0006] The present disclosure (2) is the gasket according to the present disclosure (1), wherein the polytetrafluoroethylene is modified polytetrafluoroethylene.

[0007] The present disclosure (3) is the gasket according to the present disclosure (1) or (2), wherein the polytetrafluoroethylene is a modified polytetrafluoroethylene containing a tetrafluoroethylene unit and at least one modified monomer unit selected from the group consisting of a perfluoro(alkyl vinyl ether) unit and a hexafluoropropylene unit.

[0008] The present disclosure (4) is the gasket according to the present disclosure (2) or (3), wherein the modified amount of the modified polytetrafluoroethylene is 0.001 to 1.0 mass %.

[0009] The present disclosure (5) is a gasket having a specific gravity of 2.130 or more and 2.180 or less, which is any combination with any of the present disclosures (1) to (4).

[0010] The present disclosure (6) is a gasket in any combination with any of the present disclosures (1) to (5) in contact with an electrolyte.

[0011] The present disclosure (7) is a gasket having a crystallinity of 35 to 60% and any combination with any of the present disclosures (1) to (6).

[0012] The present disclosure (8) is a gasket having a scattering intensity of 800 to 1600, which is any combination with any of the present disclosures (1) to (7).

[0013] The present disclosure (9) is an electrochemical device including a gasket in any combination with any of the present disclosures (1) to (8).

[0014] The present disclosure (10) is a gasket for an electrochemical device, which contains polytetrafluoroethylene exhibiting non-melt moldability and has a specific gravity of 2.130 or more and 2.180 or less.

[0015] The present disclosure (11) is the gasket according to the present disclosure (10), having a crystallinity of 65% or less and a scattering intensity of 800 or more.

[0016] The present disclosure (12) is a gasket for an electrochemical device, which contains polytetrafluoroethylene exhibiting non-melt moldability, has a crystallinity of 65% or less, and has a scattering intensity of 800 or more.

[0017] The present disclosure (13) is an electrochemical device including a gasket in any combination with any of the present disclosures (1) to (12) having a polytetrafluoroethylene content of 99.9 mass % or more.

[0018] The present disclosure (14) is an electrochemical device including a gasket having a specific gravity of 2.140 to 2.170 in any combination with any of the present disclosures (1) to (13).

[0019] The present disclosure (15) is an electrochemical device including a gasket in any combination with any of the present disclosures (1) to (14), in which the polytetrafluoroethylene is a homopolymer of tetrafluoroethylene or a modified PTFE having a content of modified monomer units of 0.01 to 0.10 mass% relative to the total polymerized units. Effect of the Invention

[0020] According to the present disclosure, it is possible to provide a gasket having excellent low water vapor permeability, and an electrochemical device using the same. [Brief description of the drawings]

[0021] [Figure 1] FIG. 2 is a schematic cross-sectional view showing the configuration of a portion including a gasket of an electrochemical device. [Diagram 2] FIG. 2 is a schematic cross-sectional view of a permeation test fixture used in a water vapor permeation test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0022] Conventionally, PFA and other materials have been used as gaskets with excellent low water vapor permeability. On the other hand, polytetrafluoroethylene (PTFE) has excellent chemical resistance and heat resistance, but it has been considered to be inferior in terms of low water vapor permeability. Surprisingly, it has been found that water vapor permeability can be reduced even when PTFE is used.

[0023] The present disclosure will now be described in detail.

[0024] The present disclosure provides a gasket (hereinafter also referred to as gasket (1) of the present disclosure) that contains PTFE exhibiting non-melt moldability and has a water vapor permeability coefficient of 0.020 g / 1000 hr or less.

[0025] In this specification, unless otherwise specified, gasket (1) of the present disclosure, as well as gasket (2) of the present disclosure and gasket (3) of the present disclosure described below, will be collectively referred to as the "gaskets of the present disclosure."

[0026] The gasket (1) of the present disclosure has the above-mentioned configuration, and is excellent in low water vapor permeability. In addition, since it contains PTFE, it also has excellent chemical resistance and heat resistance.

[0027] The gasket (1) of the present disclosure has a water vapor permeability coefficient of 0.020 g / 1000 hr or less, and in terms of further improving low water vapor permeability, it is preferably 0.015 g / 1000 hr or less, more preferably 0.012 g / 1000 hr or less, even more preferably 0.010 g / 1000 hr or less, even more preferably 0.009 g / 1000 hr or less, even more preferably 0.008 g / 1000 hr or less, even more preferably 0.007 g / 1000 hr or less, even more preferably 0.006 g / 1000 hr or less, particularly preferably 0.004 g / 1000 hr or less, and may be 0.0001 g / 1000 hr or more.

[0028] The water vapor permeability coefficient is determined by measuring the mass of water that permeates a circular gasket having a rectangular cross section with an outer diameter of Φ17.7 mm, an inner diameter of Φ14.3 mm, and a thickness of 1.6 mmt at a compression rate of 40% and at 80°C for 1,000 hours. The compression ratio can be calculated by the following formula. Compression rate (%) = [(thickness of gasket before compression) - (thickness of gasket in compressed state)] / (thickness of gasket before compression) x 100 When measuring using a gasket attached to an electrochemical device, the gasket is removed from the attached state and heat-treated at 150°C for 24 hours, and the thickness of the gasket after that is regarded as the thickness before the gasket is compressed, and then the thickness is measured by compressing it to the above-mentioned compression ratio. The water vapor permeability coefficient is a value measured at a compression ratio of 40%, but in terms of further improving low water vapor permeability, it is preferable to measure the value at a compression ratio of 30%, more preferably to measure the value at a compression ratio of 25%, even more preferably to measure the value at a compression ratio of 20%, and even more preferably to measure the value at a compression ratio of 15%.

[0029] The present disclosure also provides a gasket for electrochemical devices (hereinafter also referred to as gasket (2) of the present disclosure) which contains PTFE exhibiting non-melt moldability and has a specific gravity of 2.130 or more and 2.180 or less.

[0030] The gasket (2) of the present disclosure has the above-mentioned configuration, and is excellent in low water vapor permeability. In addition, since it contains PTFE, it also has excellent chemical resistance and heat resistance.

[0031] The gasket (2) of the present disclosure has a specific gravity of 2.130 or more and 2.180 or less. In order to further improve low water vapor permeability, the specific gravity is preferably 2.175 or less, more preferably 2.170 or less, even more preferably 2.165 or less, even more preferably 2.160 or less, and is preferably 2.135 or more, and more preferably 2.140 or more. The specific gravity is measured by a water displacement method in accordance with ASTM D 792. The specific gravity of the gasket of the present disclosure may be measured before or after the water vapor permeability measurement.

[0032] The specific gravity of the gasket can be adjusted by the firing conditions during molding. Increasing the rate at which the temperature is lowered during firing of the gasket reduces the degree of crystallinity and the specific gravity. A low specific gravity, i.e., a low degree of crystallinity, results in excellent low water vapor permeability. This is because a high specific gravity results in a high degree of crystallinity and a low proportion of molecular chains forming the amorphous portion, resulting in the presence of many tiny voids and a high amount of water vapor permeation in the amorphous portion. It is presumed that this results in a deterioration in the low water vapor permeability of the gasket.

[0033] The present disclosure also provides a gasket for an electric device (hereinafter also referred to as gasket (3) of the present disclosure) which contains PTFE exhibiting non-melt moldability and has a crystallinity of 65% or less and a scattering intensity of 800 or more.

[0034] The gasket (3) of the present disclosure has the above-mentioned configuration, and therefore has excellent low water vapor permeability. In addition, since it contains PTFE, it also has excellent chemical resistance and heat resistance.

[0035] The gasket (3) of the present disclosure has a crystallinity of 65% or less. In order to further improve the low water vapor permeability, the crystallinity is preferably 62% or less, more preferably 60% or less, and even more preferably 58% or less. There is no particular lower limit, but it is preferably 30% or more, more preferably 35% or more, even more preferably 38% or more, and even more preferably 40% or more. The degree of crystallinity is measured using an X-ray diffractometer (UltimaIII, manufactured by Rigaku Corporation) under the following measurement conditions using the multiple peak separation method: A measurement sample with a thickness of 40 μm or more is set in a sample holder, and the peaks of the crystalline and amorphous parts of the obtained diffraction spectrum are separated into independent peaks, and the degree of crystallinity is calculated by determining the integrated intensity (area) of each peak.

[0036] Measurement conditions [Table 1]

[0037] Gaskets with a low degree of crystallinity have excellent low water vapor permeability. It is expected that a gasket with a high degree of crystallinity will have excellent low water vapor permeability, but it was surprisingly found that a gasket with a low degree of crystallinity has excellent low water vapor permeability. This is because when the degree of crystallinity is high, the proportion of molecular chains that form the amorphous portion decreases, resulting in the existence of many tiny voids and increasing the amount of water vapor permeation in the amorphous portion. It is presumed that this results in the gasket's low water vapor permeability being deteriorated. The degree of crystallinity can be adjusted by the molding conditions of the PTFE that forms the gasket. The degree of crystallinity may be measured on the gasket after molding, or on the gasket that has been removed. This is because there is almost no change in the degree of crystallinity before and after the water vapor permeation measurement. After the water vapor permeation measurement, the scattering intensity increases, suggesting that pseudo-crystals have been formed, but since the amount of pseudo-crystals formed is small, this does not show a change in the degree of crystallinity.

[0038] The gasket (3) of the present disclosure has a scattering intensity of 800 or more. In order to further improve low water vapor permeability, the scattering intensity is preferably 850 or more, more preferably 900 or more, and even more preferably 1000 or more. There is no particular upper limit, but it is preferably 2000 or less, more preferably 1800 or less, even more preferably 1700 or less, even more preferably 1600 or less, and particularly preferably 1500 or less. The scattering intensity was measured using a small angle X-ray diffraction device (RINT2500, manufactured by Rigaku Corporation) under the following measurement conditions. -1 The scattering intensity is defined as the scattering intensity when

[0039] Measurement conditions [Table 2]

[0040] The compression ratio at the time of installation can be estimated by measuring the scattering intensity in small-angle X-ray diffraction measurements of the gasket removed from the test fixture after the water vapor permeation test. If the compression ratio is high, new pseudo-crystals are formed in the amorphous part of the PTFE that forms the gasket, and it is presumed that even after the test is completed and compression is released, the scattering intensity will be large due to the density difference between the newly formed pseudo-crystals in the PTFE and the amorphous part. Since a high degree of compression improves low water vapor permeability, measuring the scattering intensity of the gasket after installation shows that the gasket has excellent low water vapor permeability.

[0041] In order to further improve the low water vapor permeability, the gasket (2) and the gasket (3) of the present disclosure preferably have a water vapor permeability coefficient of 0.010 g / 1000 hr or less, more preferably 0.009 g / 1000 hr or less, even more preferably 0.008 g / 1000 hr or less, even more preferably 0.007 g / 1000 hr or less, even more preferably 0.006 g / 1000 hr or less, particularly preferably 0.004 g / 1000 hr or less, and may be 0.0001 g / 1000 hr or more. As described above, the water vapor permeability coefficient is a value measured at a compression ratio of 40%, but in order to further improve low water vapor permeability, it is preferable to measure the value at a compression ratio of 30%, more preferably to measure the value at a compression ratio of 25%, even more preferably to measure the value at a compression ratio of 20%, and even more preferably to measure the value at a compression ratio of 15%.

[0042] In order to further improve the low water vapor permeability, the gasket (1) of the present disclosure and the gasket (3) of the present disclosure may have a specific gravity of 2.185 or less, preferably 2.180 or less, more preferably 2.175 or less, even more preferably 2.170 or less, even more preferably 2.165 or less, even more preferably 2.160 or less, and, although there is no particular lower limit, may have a specific gravity of 2.130 or more, preferably 2.135 or more, and more preferably 2.140 or more. The specific gravity is measured by a water displacement method in accordance with ASTM D 792. The specific gravity of the gasket of the present disclosure may be measured before or after the water vapor permeability measurement.

[0043] The gasket (1) and the gasket (2) of the present disclosure preferably have a crystallinity of 65% or less, more preferably 62% or less, even more preferably 60% or less, and even more preferably 58% or less. The lower limit is not particularly limited, but is preferably 30% or more, more preferably 35% or more, even more preferably 38% or more, and even more preferably 40% or more. The crystallinity is measured by the method described above.

[0044] In order to further improve low water vapor permeability, the gasket (1) of the present disclosure and the gasket (2) of the present disclosure preferably have a scattering intensity of 800 or more, more preferably 850 or more, even more preferably 900 or more, and particularly preferably 1000 or more. There is no particular upper limit, but it is preferably 2000 or less, more preferably 1800 or less, even more preferably 1700 or less, even more preferably 1600 or less, and particularly preferably 1500 or less. The scattering intensity is measured by the method described above.

[0045] The PTFE in the gaskets of the present disclosure is non-melt formable. In this specification, being non-melt moldable means that the melt flow rate (MFR) is less than 0.10 g / 10 min, preferably less than 0.01 g / 10 min. The MFR is a value obtained in accordance with ASTM D1238 using a melt indexer, as the mass (g / 10 min) of polymer flowing out per 10 min from a nozzle having an inner diameter of 2.095 mm and a length of 8 mm at 372° C. and a load of 5000 g (total load).

[0046] The PTFE may be a homopolymer of tetrafluoroethylene (TFE) or a modified PTFE. The modified PTFE is preferred because it has a lower water vapor permeability, and the homopolymer of tetrafluoroethylene or the modified PTFE having a content of modified monomer units of 0.01 to 0.10% by mass based on the total polymerized units is also preferred.

[0047] The modified PTFE preferably contains TFE units and 1.0% by mass or less of modified monomer units. The amount of TFE units may be 99.0% by mass or more. The modified PTFE may be composed of only TFE units and modified monomer units.

[0048] In the above modified PTFE, the content of the modified monomer unit (modification amount) is preferably in the range of 0.00001 to 1.0 mass% based on the total polymerized units, in order to further improve the low water vapor permeability. The lower limit of the content of the modified monomer unit is more preferably 0.0001 mass%, more preferably 0.001 mass%, even more preferably 0.005 mass%, and especially preferably 0.010 mass%. The upper limit of the content of the modified monomer unit is preferably 0.90 mass%, more preferably 0.80 mass%, more preferably 0.50 mass%, even more preferably 0.40 mass%, even more preferably 0.30 mass%, even more preferably 0.20 mass%, and especially preferably 0.10 mass%. In this specification, the modified monomer unit means a portion of the molecular structure of PTFE that is derived from a modified monomer.

[0049] The content of each of the above-mentioned polymer units can be calculated by appropriately combining NMR, FT-IR, elemental analysis, and X-ray fluorescence analysis depending on the type of monomer.

[0050] The above-mentioned modified monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene [HFP], hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride [VDF], perhaloolefins such as chlorotrifluoroethylene [CTFE], perfluorovinyl ethers, perfluoroallyl ethers, (perfluoroalkyl)ethylenes, ethylenes, etc. The modified monomers used may be one type or multiple types.

[0051] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorovinyl ethers represented by the following general formula (A): CF2=CF-ORf 1 (A) (In the formula, Rf 1 represents a perfluoro organic group. ) and the like. In this specification, the above-mentioned "perfluoro organic group" means an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The above-mentioned perfluoro organic group may have an ether oxygen.

[0052] The perfluorovinyl ether may be, for example, a compound represented by the general formula (A) in which Rf 1 and perfluoro(alkyl vinyl ether) [PAVE], which is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5.

[0053] Examples of the perfluoroalkyl group in the PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group.

[0054] The perfluorovinyl ether further includes, in the above general formula (A), Rf 1 is a perfluoro(alkoxyalkyl) group having 4 to 9 carbon atoms, Rf 1 is the following formula:

[0055] [ka]

[0056] (wherein m represents 0 or an integer of 1 to 4), Rf 1 is the following formula:

[0057] [ka]

[0058] (wherein n represents an integer of 1 to 4).

[0059] The (perfluoroalkyl)ethylene [PFAE] is not particularly limited, and examples thereof include (perfluorobutyl)ethylene [PFBE] and (perfluorohexyl)ethylene.

[0060] Examples of hydrogen-containing fluoroolefins include CH2=CF2, CFH=CH2, CFH=CF2, CH2=CFCF3, CH2=CHCF3, CHF=CHCF3 (E-form), and CHF=CHCF3 (Z-form).

[0061] The perfluoroallyl ether may, for example, be a compound represented by the general formula (B): CF2=CF-CF2-ORf 2 (B) (In the formula, Rf 2 represents a perfluoro organic group.

[0062] Above Rf 2is preferably a perfluoroalkyl group having 1 to 10 carbon atoms or a perfluoroalkoxyalkyl group having 1 to 10 carbon atoms. The perfluoroallyl ether is preferably at least one selected from the group consisting of CF2=CF-CF2-O-CF3, CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, more preferably at least one selected from the group consisting of CF2=CF-CF2-O-C2F5, CF2=CF-CF2-O-C3F7, and CF2=CF-CF2-O-C4F9, and further preferably CF2=CF-CF2-O-CF2CF2CF3.

[0063] As the above-mentioned modified monomer, in terms of further improving the low water vapor permeability, at least one selected from the group consisting of PAVE, PFAE and HFP is preferable, at least one selected from the group consisting of PAVE and HFP is more preferable, PAVE is even more preferable, and perfluoro(propyl vinyl ether) [PPVE] is even more preferable.

[0064] The PTFE may have a core-shell structure. For example, the PTFE having a core-shell structure may be modified PTFE having a core of high molecular weight PTFE and a shell of lower molecular weight PTFE or modified PTFE in a particle. For example, the modified PTFE described in JP-T-2005-527652 may be used.

[0065] In order to further improve the low water vapor permeability, the above-mentioned PTFE preferably has a heat of crystallization measured by a differential scanning calorimeter (DSC) of 25 J / g or more, more preferably 26 J / g or more, and even more preferably 27 J / g or more, and preferably 33 J / g or less, more preferably 32 J / g or less, even more preferably 30 J / g or less, and particularly preferably 29 J / g or less. The heat of crystallization is measured by the following method. Approximately 3 mg of the sample is weighed out and placed in a dedicated aluminum pan. Using an X-DSC7000 (Hitachi High-Tech Science Corporation), the temperature is raised to 380°C at a rate of 10°C / min under a nitrogen atmosphere, held for 1 minute, and then cooled to 250°C at a rate of 10°C / min to measure the heat of crystallization at the crystallization point. The value of the heat of crystallization is determined by drawing a line from 275°C to 330°C on the resulting DSC chart, and the area enclosed by the curve including the peak and the line.

[0066] The gasket of the present disclosure may contain components other than the PTFE, but is preferably substantially made of the PTFE. This allows the effects of the PTFE to be significantly exhibited. "Substantially made of the PTFE" means that the PTFE content is 95.0% by mass or more relative to the gasket. The PTFE content of the gasket is preferably 98.0 mass% or more, more preferably 99.0 mass% or more, even more preferably 99.5 mass% or more, particularly preferably 99.9 mass% or more, and most preferably 99.95 mass% or more. It is also preferred that the gasket of the present disclosure consists solely of the above-mentioned PTFE.

[0067] Gaskets of the present disclosure preferably exhibit non-melt formability.

[0068] In order to further improve the low water vapor permeability of the gasket of the present disclosure, the compression rate when fitted is preferably 10% or more, more preferably 12% or more, even more preferably 17% or more, even more preferably 25% or more, particularly preferably 35% or more, and is preferably 65% ​​or less, and more preferably 60% or less. The compression ratio can be calculated by the following formula. Compression rate (%) = [(thickness of gasket before compression) - (thickness of gasket in compressed state)] / (thickness of gasket before compression) x 100 When measurements are made using a gasket attached to an electrochemical device, the gasket is removed from the attached state and heat-treated at 150°C for 24 hours, and the thickness of the gasket after that is regarded as the thickness before the gasket is compressed, and the compression ratio is measured.

[0069] The gasket of the present disclosure can be produced by forming raw PTFE into a desired shape and sintering it. The form of the raw PTFE is not limited and may be a powder, a dispersion liquid, or the like, but is preferably a powder.

[0070] The standard specific gravity (SSG) of the above-mentioned raw material PTFE is preferably 2.130 or more, more preferably 2.135 or more, and even more preferably 2.140 or more, and is preferably 2.180 or less, more preferably 2.175 or less, even more preferably 2.170 or less, even more preferably 2.165 or less, and particularly preferably 2.160 or less. The SSG is measured by a water displacement method according to ASTM D 792 using a sample molded according to ASTM D 4895 89. By setting the SSG within the above range, the water vapor permeability coefficient can be easily set within the above range.

[0071] The raw PTFE can be produced by emulsion polymerization or suspension polymerization, and is preferably produced by suspension polymerization.

[0072] The emulsion polymerization can be carried out by a known method. For example, in the presence of an anionic fluorine-containing surfactant and a polymerization initiator, the emulsion polymerization of monomers (TFE and optionally modified monomers) required for forming the PTFE is carried out in an aqueous medium to obtain an aqueous dispersion containing the PTFE particles (primary particles). In the emulsion polymerization, a chain transfer agent, a buffer, a pH adjuster, a stabilizing aid, a dispersion stabilizer, a radical scavenger, etc. may be used as necessary.

[0073] The obtained aqueous dispersion is coagulated to obtain a wet powder, and then the wet powder is dried to obtain a raw material PTFE powder. The coagulation and drying can be performed by a known method.

[0074] Suspension polymerization can be carried out, for example, by charging a monomer such as TFE, an aqueous medium, and other additives as necessary into a reactor, stirring the contents of the reactor, maintaining the reactor at a predetermined polymerization temperature, and then adding a predetermined amount of a polymerization initiator to start the polymerization reaction. After the start of the polymerization reaction, a monomer such as TFE, a polymerization initiator, a chain transfer agent, and the like may be additionally added depending on the purpose.

[0075] The suspension-polymerized particles thus obtained may be washed and then pulverized, or the suspension-polymerized particles thus obtained may be pulverized while being washed, to prepare pulverized particles.

[0076] The wet ground particles may be dehydrated and further dried for the purpose of removing moisture from the ground particles obtained by grinding.

[0077] After the suspension polymerized particles are pulverized, the pulverized particles obtained may be classified by a known method such as air classification.

[0078] The resulting pulverized particles may be granulated by a known granulation method.

[0079] By adjusting the polymerization and post-treatment conditions, the physical properties of the resulting PTFE can be adjusted. For example, in emulsion polymerization, the endothermic peak temperature can be increased, the standard specific gravity can be lowered, and the melt viscosity can be increased by reducing the amount of polymerization initiator used, reducing the amount of chain transfer agent used, and using a radical scavenger. In the post-treatment of emulsion polymerization, the decomposition temperature can be increased by setting the drying temperature at 150° C. or higher. In suspension polymerization, the endothermic peak temperature can be increased, the standard specific gravity can be lowered, and the melt viscosity can be increased by reducing the amount of polymerization initiator used, or by reducing the amount of chain transfer agent used, or preferably by not using any of the agent at all. In post-treatment, the decomposition temperature can be increased by washing the polymer and setting the drying temperature to 150°C or higher.

[0080] Regarding the method of molding raw PTFE, when using the powder obtained by emulsion polymerization, for example, the raw PTFE powder can be mixed with an extrusion aid and paste extrusion molded. The extrusion aid can be removed by drying. It is also preferable to compression mold the raw PTFE powder.

[0081] When the powder obtained by suspension polymerization is used, a molding method such as compression molding, ram extrusion molding, isostatic compression molding, etc. can be used. The PTFE molded body may be processed by machining such as cutting to produce a molded body having a desired shape. For example, a PTFE sheet can be obtained by cutting the PTFE molded body.

[0082] The calcination can be carried out, for example, by heating at a temperature of 350 to 380° C. for 0.5 to 50 hours.

[0083] The firing may include a section in which the temperature drop rate from 370° C. to 250° C. is 25° C. / hr or more, and preferably includes a section in which the temperature drop rate is greater than 25° C. / hr. The above section is preferably included in the cooling step after heating. The cooling rate is more preferably 30° C. / hr or more, even more preferably 45° C. / hr or more, even more preferably 55° C. / hr or more, and particularly preferably 65° C. / hr or more. Cooling (quenching) by directly immersing in water is also preferred. By setting the temperature decreasing rate within the above range, the water vapor permeability coefficient and the heat of crystallization can be easily set within the above range. When using a raw material PTFE having a relatively high molecular weight, it is preferable to set the temperature decreasing rate to a low level.

[0084] The gasket of the present disclosure is a member used to prevent leakage of liquid or gas, or intrusion of liquid or gas from the outside, in an object (such as an apparatus) to which it is applied.

[0085] The shape of the gasket of the present disclosure is not particularly limited and may be, for example, an annular shape. The gasket of the present disclosure may have a circular, oval, rectangular shape with rounded corners, or the like in a plan view and may have a through hole in the center.

[0086] The gasket of the present disclosure has excellent low water vapor permeability and can therefore be used in any application requiring prevention of water leakage or intrusion, and is particularly suitable for use in electrochemical devices.

[0087] A use of a gasket according to an embodiment of the present disclosure in an electrochemical device will be described with reference to the drawings.

[0088] 1, an electrochemical device 10 (for example, a sealed prismatic secondary battery) includes an outer can (not shown) and a lid 1. An electric element (not shown) such as a power generator is housed inside the outer can, and the opening of the outer can is hermetically sealed with the lid 1. The lid 1 is provided with an external terminal 2 (positive terminal or negative terminal), and externally generated power is supplied to an electric element via the external terminal 2 for storage, and also supplied to an external load.

[0089] A gasket 3 for sealing and insulation is provided between the external terminal 2 and the lid 1. The gasket 3 corresponds to the gasket of the present disclosure. Moreover, in order to electrically insulate the external terminal 2 from the lid 1, an insulating plate 4 is provided on the lid 1. The external terminal 2 has a terminal head 21 having a rectangular parallelepiped block shape, and a cylindrical shaft portion 22. The shaft portion 22 protrudes from the lower surface of the terminal head 21 (on the inner side of the electrochemical device).

[0090] As shown in FIG. 1, the gasket 3 has a cylindrical portion 31, a flange portion 32 extending radially from one opening of the cylindrical portion 31, and a side wall portion 33 rising from the periphery of the flange portion 32.

[0091] The cylindrical portion 31 is fitted onto the shaft portion 22 of the external terminal 2, and the inner peripheral surface of the cylindrical portion 31 abuts against the outer peripheral surface of the shaft portion 22. The cylindrical portion 31 is also inserted into the through hole of the lid 1, and the outer peripheral surface of the cylindrical portion 31 abuts against the inner peripheral surface of the through hole of the lid 1.

[0092] The flange portion 32 is sandwiched between the lid 1 and the external terminal 2 , with one contact surface of the flange portion 32 contacting the lower surface of the external terminal 2 and the other contact surface of the flange portion 32 contacting the surface of the lid 1 .

[0093] With the cylindrical portion 31 and the flange portion 32 of the gasket 3 in a compressed state, the gasket 3 comes into contact with the external terminal 2 and the lid 1, thereby ensuring the hermeticity of the electrochemical device.

[0094] Electrochemical devices to which the gasket of the present disclosure can be applied include batteries, capacitors, and the like. The battery may be a secondary battery such as a lithium ion battery. The capacitor is not particularly limited, but is preferably an electrochemical capacitor. Examples of the electrochemical capacitor include an electric double layer capacitor, a hybrid capacitor, and a redox capacitor. Examples of the hybrid capacitor include a sodium ion capacitor, a lithium ion capacitor, and a magnesium ion capacitor. Among these, an electric double layer capacitor is particularly preferred.

[0095] The gasket of the present disclosure can be suitably used as a gasket for batteries, and can be particularly suitably used as a gasket for secondary batteries such as lithium ion batteries.

[0096] The secondary battery may be a secondary battery that uses an electrolyte solution, or may be a solid-state secondary battery. In this specification, the solid-state secondary battery may be a secondary battery containing a solid electrolyte, and may be a semi-solid secondary battery containing a solid electrolyte and a liquid component as the electrolyte, or may be an all-solid-state secondary battery containing only a solid electrolyte as the electrolyte.

[0097] The gasket of the present disclosure is preferably in contact with the electrolyte, i.e., has a contact surface with the electrolyte. Since the gasket of the present disclosure has excellent low water vapor permeability, when used in contact with the electrolyte, it can suppress the intrusion of water into the electrolyte. The electrolyte referred to here includes not only the electrolyte itself provided in the electrochemical device, but also a substance derived from the electrolyte, and may be a liquid, a solid, or a gas. The gas includes, for example, an electrolyte solution that has evaporated, or a gas generated by decomposition of the electrolyte solution during charging and discharging.

[0098] The electrochemical device according to the present disclosure preferably includes a non-aqueous electrolyte. The gasket according to the present disclosure is preferably used in a state of contact with the non-aqueous electrolyte, i.e., has a surface in contact with the non-aqueous electrolyte.

[0099] The non-aqueous electrolyte may be prepared by dissolving a known electrolyte salt in a known organic solvent for dissolving electrolyte salts.

[0100] The organic solvent for dissolving the electrolyte salt is not particularly limited, and one or more of known hydrocarbon solvents such as propylene carbonate, ethylene carbonate, butylene carbonate, γ-butyrolactone, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate; and fluorine-based solvents such as fluoroethylene carbonate, fluoroether, and fluorinated carbonate can be used.

[0101] Examples of electrolyte salts include LiClO4, LiAsF6, LiBF4, LiPF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiCl, LiBr, CH3SO3Li, CF3SO3Li, cesium carbonate, etc., and LiPF6, LiBF4, LiN(SO2CF3)2, LiN(SO2C2F5)2, or combinations of these are particularly preferred because of their good cycle characteristics.

[0102] The concentration of the electrolyte salt is preferably 0.8 mol / L or more, more preferably 1.0 mol / L or more. The upper limit depends on the organic solvent for dissolving the electrolyte salt, but is usually 1.5 mol / L.

[0103] The solid electrolyte used in the solid secondary battery may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte. In particular, the sulfide-based solid electrolyte has the advantage of being flexible.

[0104] The sulfide-based solid electrolyte is not particularly limited, and examples thereof include Li2S-P2S5, Li2S-P2S3, Li2S-P2S3-P2S5, Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, LiI-Li2S-SiS2-P2S5, Li2S-SiS2-Li4SiO4, Li2S-SiS2-Li3PO4, Li3PS4-Li4GeS4, Li 3.4 P 0.6 S 0.4 S4, Li 3.25 P 0.25 Ge 0.76 S4, Li 4-x Ge 1-x P x S4(x=0.6~0.8), Li 4+y Ge 1-y Ga y S4(y=0.2~0.3), LiPSCl, LiCl, Li 7-x-2y P.S. 6-x-y Cl x (0.8≦x≦1.7, 0 <y≦-0.25x+0.5)、Li 10 SnP2S 12Any one selected from the above, or a mixture of two or more of them, can be used.

[0105] The sulfide-based solid electrolyte preferably contains lithium. The sulfide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0106] The oxide-based solid electrolyte is preferably a compound that contains an oxygen atom (O), has the ionic conductivity of a metal belonging to Group 1 or 2 of the periodic table, and has electronic insulation properties.

[0107] Specific examples of compounds include Li xa La ya TiO3 [xa=0.3~0.7, ya=0.3~0.7] (LLT), Li xb La yb Zr zb M bb mb O nb (M bb is at least one of the elements Al, Mg, Ca, Sr, V, Nb, Ta, Ti, Ge, In, and Sn, where xb satisfies 5≦xb≦10, yb satisfies 1≦yb≦4, zb satisfies 1≦zb≦4, mb satisfies 0≦mb≦2, and nb satisfies 5≦nb≦20. ), Li xc B yc M cc zc O nc (M cc is at least one element selected from C, S, Al, Si, Ga, Ge, In, and Sn, where xc satisfies 0≦xc≦5, yc satisfies 0≦yc≦1, zc satisfies 0≦zc≦1, and nc satisfies 0≦nc≦6. ), Li xd (Al,Ga) yd (Ti,Ge) zd S ad P md O nd (where 1≦xd≦3, 0≦yd≦2, 0≦zd≦2, 0≦ad≦2, 1≦md≦7, 3≦nd≦15), Li(3-2xe) M ee xe D ee O(xe is a number between 0 and 0.1, and M ee represents a divalent metal atom. ee represents a halogen atom or a combination of two or more halogen atoms. xf S yf O zf (1≦xf≦5, 0 <yf≦3、1≦zf≦10)、Li xg S yg O zg (1≦xg≦3, 0 <yg≦2、1≦zg≦10)、Li3BO3-Li2SO4、Li2O-B2O3-P2O5、Li2O-SiO2、Li6BaLa2Ta2O 12 , LiPO (4-3 / 2w) N w (w is w<1), Li with LISICON (Lithium super ionic conductor) type crystal structure 3.5 Zinc 0.25 GeO4, La with perovskite crystal structure 0.51 Li 0.34 TiO 2.94 , La 0.55 Li 0.35 TiO3, LiTi2P3O with NASICON (sodium super ionic conductor) type crystal structure 12 , Li 1+xh+yh (Al,Ga) xh (Ti,Ge) 2-xh S yh P 3-yh O 12 (where 0≦xh≦1, 0≦yh≦1), Li7La3Zr2O with a garnet-type crystal structure 12 (LLZ) and others. Ceramic materials in which elements have been substituted for LLZ are also known. For example, Li 6.24 La3Zr2Al 0.24 O 11.98 , Li 6.25 Al 0.25 La3Zr2O 12 and Li substituted with Ta 6.6 La3Zr 1.6 Ta0.4 O 12 , Li substituted with Nb 6.75 La3Zr 1.75 Nb 0.25 O 12 Other examples include LLZ-based ceramic materials in which at least one of Mg (magnesium) and A (A is at least one element selected from the group consisting of Ca (calcium), Sr (strontium), and Ba (barium)) is substituted for LLZ. Phosphorus compounds containing Li, P, and O are also desirable. For example, lithium phosphate (Li3PO4), LiPON, LiPOD, in which part of the oxygen in lithium phosphate is substituted with nitrogen, etc. 1 (D 1 is at least one selected from Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Nb, Mo, Ru, Ag, Ta, W, Pt, Au, etc. In addition, LiA 1 ON(A 1 is at least one selected from Si, B, Ge, Al, C, Ga, etc. Specific examples include Li2O-Al2O3-SiO2-P2O5-TiO2-GeO2 and Li2O-Al2O3-SiO2-P2O5-TiO2.

[0108] The oxide-based solid electrolyte preferably contains lithium. The oxide-based solid electrolyte containing lithium is used in a solid-state battery that uses lithium ions as a carrier, and is particularly preferred in terms of electrochemical devices having a high energy density.

[0109] The oxide-based solid electrolyte is preferably an oxide having a crystalline structure. Oxides having a crystalline structure are particularly preferred in terms of good Li-ion conductivity. Examples of oxides having a crystalline structure include perovskite-type (La 0.51 Li 0.34 TiO 2.94 etc.), NASICON type (Li 1.3 Al 0.3 Ti 1.7 (PO4)3), garnet type (Li7La3Zr2O12 (LLZ), etc. Among these, the garnet type is preferred.

[0110] The present disclosure also includes an electrochemical device including the gasket of the present disclosure.

[0111] Although the embodiments have been described above, it will be understood that various changes in form and details are possible without departing from the spirit and scope of the claims. EXAMPLES

[0112] The present disclosure will now be described in more detail with reference to examples, but the present disclosure is not limited to these examples.

[0113] Various physical properties were measured by the following methods.

[0114] <Modified monomer content> The PPVE content was determined by press-molding the sample to produce a thin-film disk, measuring the infrared absorbance of the thin-film disk using FT-IR, and then measuring the PPVE content at 995 cm -1 Absorbance at / 935cm -1 The absorbance ratio was calculated by multiplying the absorbance ratio at

[0115] <Standard specific gravity (SSG)> Using samples molded in accordance with ASTM D4895 89, the measurement was performed by the water displacement method in accordance with ASTM D 792.

[0116] <Melt moldability> According to ASTM D1238, the mass of polymer flowing out of a nozzle with an inner diameter of 2.095 mm and a length of 8 mm per 10 minutes was measured at 372°C and a load of 5000 g (total load) using a melt indexer. MFR of 0.10 g / 10 min or more was deemed to be melt moldable, and MFR of less than 0.10 g / 10 min was deemed not to be melt moldable (non-melt moldable).

[0117] Gasket A PTFE powder exhibiting non-melt moldability (modified PTFE containing 0.08% by mass of PPVE units obtained by suspension polymerization, SSG = 2.150) was compression molded under molding conditions of a pressure of 30 MPa and a holding time of 5 minutes, and the temperature was raised to 370°C at a rate of 50°C / hr in an electric furnace, and heat treatment was carried out at 370°C for 5.5 hours. Thereafter, it was cooled to room temperature at a rate of 50°C / hr to obtain annular gasket A with a square cross section, inner diameter Φ14.3 mm x outer diameter Φ17.7 mm x height 1.6 mm.

[0118] Gasket B An annular gasket B was obtained in the same manner as gasket A, except that the cooling rate during cooling was set to about 300° C. / hr by immersing the heat-treated molded body in ice water.

[0119] Gasket C An annular gasket C was obtained in the same manner as gasket A, except that the cooling rate was 25° C. / hr.

[0120] Gasket D An annular gasket D was obtained in the same manner as in gasket C, except that a homopolymer of TFE (SSG=2.165) obtained by suspension polymerization was used as the PTFE powder exhibiting non-melt moldability.

[0121] Gasket E An annular gasket E was obtained in the same manner as gasket C, except that modified PTFE (PPVE content 0.08 mass%, SSG = 2.160) obtained by suspension polymerization was used as the PTFE powder exhibiting non-melt moldability.

[0122] The obtained gasket was used to measure the water vapor permeability coefficient by the following method. After the water vapor permeability test, the gasket was removed from the test jig and the specific gravity, crystallinity, and scattering intensity of the gasket were measured. The results are shown in Table 5.

[0123] <Water vapor permeability test> 2, 2 g of water 42 was placed in an aluminum alloy cup 41. A gasket 47 was placed between the cup 41 and a gasket compression jig 43, and a lid 44 was fastened with a bolt 45 to compress the gasket 47. A spacer 46 was placed between the lid 44 and the cup 41, and the compression rate of the gasket 47 was adjusted to 15% in Example 1 and Comparative Example 1, and 40% in Examples 2 to 6. The compression ratio was calculated from the following formula. (Gasket compression rate (%))={1-(distance of the gap (gasket placement portion) between cup 41 and gasket compression jig 43) / (height of gasket before compression)}×100 The mass of the permeation test jig 40 thus obtained was measured. The permeation test jig 40 was placed in an electric furnace at 80°C, and after leaving it for 1000 hours, it was taken out and left at room temperature for 2 hours, after which the mass was measured. The water vapor permeability coefficient was calculated by the following formula. This operation was repeated three times to calculate the average value of the water vapor permeability coefficient. The average value is shown in Table 5. Water vapor permeability coefficient (g / 1000hr) = (mass of permeability test fixture before heating) - (mass of permeability test fixture after heating)

[0124] <Specific gravity> The measurement was performed by the water displacement method according to ASTM D 792.

[0125] <Crystallization degree> The crystallinity was measured using an X-ray diffractometer (UltimaIII, Rigaku Corporation) under the following measurement conditions using the multiple peak separation method: A measurement sample with a thickness of 40 μm or more was set in a sample holder, and the peaks of the crystalline and amorphous parts of the obtained diffraction spectrum were separated into independent peaks, and the crystallinity was calculated by determining the integrated intensity (area) of each peak.

[0126] Measurement conditions [Table 3]

[0127] <Scattering intensity> The scattering intensity was measured using a small angle X-ray diffraction device (RINT2500, manufactured by Rigaku Corporation) under the following measurement conditions. -1 The scattering intensity was determined as the case where

[0128] Measurement conditions [Table 4]

[0129] [Table 5] [Explanation of symbols]

[0130] 10: Electrochemical devices 1: Lid 2: External terminal 21:Terminal head 22: Shaft 3: Gasket 31: Cylindrical part 32: Flange part 33: Side wall 4: Insulating plate 40: Transmission test fixture 41: Cup 42:Water 43: Gasket compression tool 44: Lid 45: Bolt 46: Spacer 47: Gasket

Claims

1. A gasket comprising polytetrafluoroethylene exhibiting non-melt moldability and having a water vapor permeability coefficient of 0.020 g / 1000 hr or less.

2. 2. The gasket of claim 1, wherein said polytetrafluoroethylene is a modified polytetrafluoroethylene.

3. 3. The gasket according to claim 2, wherein the polytetrafluoroethylene is a modified polytetrafluoroethylene containing a tetrafluoroethylene unit and at least one modified monomer unit selected from the group consisting of a perfluoro(alkyl vinyl ether) unit and a hexafluoropropylene unit.

4. 4. The gasket according to claim 2, wherein the modified polytetrafluoroethylene has a modification amount of 0.001 to 1.0% by mass.

5. 3. The gasket according to claim 1, having a specific gravity of 2.130 or more and 2.180 or less.

6. 3. The gasket of claim 1 or 2 in contact with an electrolyte.

7. 3. The gasket according to claim 1, having a crystallinity of 35 to 60%.

8. 3. The gasket according to claim 1, wherein the scattering intensity is 800 to 1,600.

9. An electrochemical device comprising the gasket according to claim 1 or 2.

10. A gasket for an electrochemical device, comprising polytetrafluoroethylene exhibiting non-melt moldability, and having a specific gravity of 2.130 or more and 2.180 or less.

11. 11. The gasket according to claim 10, having a crystallinity of 65% or less and a scattering intensity of 800 or more.

12. A gasket for an electrochemical device comprising polytetrafluoroethylene exhibiting non-melt moldability, having a crystallinity of 65% or less, and a scattering intensity of 800 or more.

13. 13. The gasket according to claim 1, 2, 10, 11 or 12, wherein the polytetrafluoroethylene content is 99.9 mass % or more.

14. The gasket according to claim 1, 2, 10, 11 or 12, having a specific gravity of 2.140 to 2.

170.

15. 13. The gasket according to claim 1, 2, 10, 11 or 12, wherein the polytetrafluoroethylene is a homopolymer of tetrafluoroethylene or a modified PTFE having a content of modified monomer units of 0.01 to 0.10% by mass based on the total polymerized units.

Citation Information

Patent Citations

  • Gasket for fuel cell and fuel cell using it, and mold for processing gasket

    JP2005019109A

  • Fluorine-containing copolymer

    WO2022181827A1

  • Method for producing polytetrafluoroethylene powder, and polytetrafluoroethylene powder

    WO2023277137A1

  • Power storage device

    JP2017174732A

  • Power storage body and gasket

    JP2021141045A